Perspektif Rusia Tentang Hubungan Internasional Pasca Perang Dingin - Umar Suryadi Bakry (Parahyangan Center for International Studies, 2017)
After the Soviet break-up and the Marxist regime collapsed, many of alternative notions emerged in the academic community in Russia, including alternative ideas in the field of International Relations (IR). A number of Russian IR scholars attempted to reconstruct the theories of IR, not just the IR theories that developed in Russia during the era of Marxism, but also against Western IR theories. Although the post-Cold War aspirations to create a distinct national school of International Relations in Russia, but these efforts are not free from the ideology and political goal that directing and guiding Russian foreign policy. Even, IR scholars in Russia have come to shared with the Russian government in terms of building the IR theories with the Russian characteristics, especially in challenging Western hegemony in the social sciences and international relations. This article tries to elaborate three intellectual traditions of international relations that developed in Russia, namely Westernism, Statism, and Civilizationism. Westernizer IR heavily influenced by Western liberalism, Statism more inspired by the realism, while Civilizationism is more of a hybrid between the constructivism and Russian essentialism.